Interpretation of the Good and the Evil by Representatives of Catholicism - Poška, Algirdas (Problemos, 1979)
The anti-Communist conception of the Evil once propagated by clericals in Lithuania was based on the interpretation of spiritual values, traditional for objective idealism, denying real needs of man. The principle of pan-religiosity has become a methodological postulate of moral depreciation of “atheistic Communism”.